The Effect of Molasses in Cultivating Vanamei Shrimp (Litopenaeus vannamei) by a Shrimp Cultivation System without Water Changes on Conventional Feed Decrease - Pohan Panjaitan; Helentina Manullang (Universitas Labuhanbatu, 2024)
The primary challenge in developing the intensive hatchery of white shrimp (Litopenaeus vannamei) farming industry is the accumulation of nitrogen and organic toxins. The shrimp pond unit's feed serves as the source of inorganic nitrogen. This study investigated the effect of molasses in cultivating vaname shrimp (Litopenaeus vannamei) by a shrimp cultivation system without water changes on conventional feed decrease. This was done because molasses has the potential to stimulate the growth of heterotrophic bacteria in shrimp pond units without air exchange. In addition to their role in controlling inorganic nitrogen, heterotrophic bacteria also serve as a natural food source for the shrimp in the pond unit. This study employed an experimental method, testing five treatments using molasses and varying the concentration of conventional feed. This study found that the best treatment was a combination of molasses and 75% conventional feed, with a C:N ratio of feed = 20.0:1. This study found that the rate of decreasing natural feed provision had a significant effect on shrimp growth rate, feed conversion ratio, and quality parameters in the model without air exchange